Pengaruh Minyak Sacha Inchi (Plukenetia volubilis L.) terhadap Kadar MDA Plasma Tikus Wistar Diinduksi Klorpirifos - Rahayu, Putri; Tajudin, Tatang; Pertiwi, Yuniariana (Universitas Muhammadiyah Prof. DR. HAMKA, 2026)
The use of chlorpyrifos remains prevalent in Indonesia, and excessive exposure can trigger oxidative stress, as indicated by increased Malondialdehyde (MDA) levels. Sacha inchi oil (Plukenetia volubilis L.) contains antioxidant compounds that may mitigate oxidative stress. This study investigated the effect of sacha inchi oil on plasma MDA concentrations, Body Weight (BW), and clinical parameters in male Wistar rats exposed to chlorpyrifos. Thirty rats were allocated to five groups (n=6 per group): a normal control, a negative control (chlorpyrifos 10 mg/kg BW/day), and three treatment groups receiving sacha inchi oil orally at doses of 1, 2, and 4 mL/kg BW/day for 28 days. Plasma MDA levels were measured using the TBARS method with spectrophotometric detection at 532 nm, and data were analysed by One-Way ANOVA followed by Tukey’s HSD test. Chlorpyrifos exposure increased MDA levels (18.83 nmol/mL) compared with the normal control, whereas sacha inchi oil reduced MDA levels in a dose-dependent manner to 11.32, 8.98, and 3.90 nmol/mL (p<0.05). Supplementation promoted BW gain and ameliorated clinical manifestations, including lethargy, alopecia, and increased respiratory rate, with no mortality observed in treated groups. Sacha inchi oil exhibited protective effects against chlorpyrifos-induced oxidative stress, demonstrating maximal efficacy at 4 mL/kg BW/day.